Arnotts goes global managing change in large organisations - Loftus-Hills, Jeremy; Shortal, Justin; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
This program looks at Arnott's response to pressures to go global, and its attempts to become a world class manufacturer by bridging the gap between mass production and lean manufacturing.
Narrator, Justin Shortal
Keywords: Arnotts Ltd; Corporate culture -- Australia; Organizational change -- Australia